Antiphospholipid syndrome (APS): from pathogenesis to treatment - Levy, Roger (Henry Stewart Talks, 2010)
History: fetal loss and LAC, The use of anti-cardiolipin antigen, GPL and past obstetric history, The primary antiphospholipid syndrome (pAPS), Causes of thromboses in SLE, Congenital thrombophilias, APS classification criteria, Anti-cardiolipin test (aCL), Autoimmunity, Lupus and APS, Thrombotic microangiopathy (MAPS), The Lucio phenomenon, Pathogenesis, CNS involvement in APS, Snnedon's syndrome, Neural injury pathogenesis in APS animal models, Management of APS, Asymptomatic aPL, Thrombosis treatment, INR recommendations, Thrombocytopenia, Obstetric management of APS, Advantages and disadvantages of heparin, Pregnancy and coumadin; clinical study, APS and preeclampsia, HCQ in SLE pregnancy: clinical study, Thrombocytopenia during pregnancy, Catastrophic APS, Alternative therapies, Vaccination as an APS triggering factor, Thromboembolism and antipsychotics, Lung adenocarcinoma and thrombosis, The future of APS treatment, Ethical issues